The Influence of Capital Intensity, Executive Compensation, Political Connections, Profitability, and Leverage on Tax Aggressiveness (Empirical Study on the Mining Sector Listed on the Indonesia Stock Exchange in 2020-2023) - Radhika Santriafi; Erna Setiany (Universitas Mercu Buana, 2024)
Tax planning actions using methods that are classified as legal (tax avoidance) or illegal (tax evasion) with the aim of reducing the tax burden are called tax aggressiveness. The aim of this research is to analyze the influence of capital intensity, executive compensation, political connections, profitability, and leverage on tax aggressiveness (empirical study of the mining sector listed on the Indonesian Stock Exchange in 2020-2023). The sample obtained was 34 companies using a purposive sampling method over a period of 4 years so that the total data studied was 136. The data analysis technique in this research was multiple linear regression analysis. The results of the analysis show that capital intensity has a negative effect on tax aggressiveness, executive compensation has little effect on tax aggressiveness, political connections have no effect on tax aggressiveness, profitability has no effect on tax aggressiveness, and leverage has a positive effect on tax aggressiveness.